Inside the sustainable development goals : from fighting poverty to saving the world - Orosz, Adele (Routledge studies in sustainable development, 2025)
The Sustainable Development Goals (SDGs) came with bold promises: ending poverty, saving the planet, and making this world a better place by 2030. But being in the second halftime, there is too little progress and too many setbacks. Drawing on the expertise of an author who has been actively involved in negotiating and later implementing the SDGs, this book offers a unique insider view into the behind-the-scenes processes. It relates the SDGs and their aims of fighting poverty and achieving sustainability to the bigger picture of politics, economics, and vested interests, breaking down dependencies and alliances, expectations and motives. It uncovers and dissects the politics and interests that shaped the SDGs from the very beginning, as well as the drivers behind propelling or curtailing sustainable development.This book is an indispensable and comprehensive guide to the SDGs. It outlines where they came from, how they are being implemented, the main lessons learned so far, and what to conclude for the years ahead. As the deadline of 2030 is close, and discussions about what should come after the SDGs are imminent, this book is among the first to draw conclusions for the post-2030 era, what to expect, and what to demand from a potential successor agenda.This book addresses policymakers, practitioners, researchers, and students alike, as well as anyone interested in poverty, environment, and sustainability. Written in a highly accessible style, this book also breaks down the United Nations and its processes and institutions, how they are enabling but also limiting the SDGs and the sustainability agenda in general.